A COMPARATIVE STUDY ON THE FORMATION OF GAY LANGUAGE WORDS AND UTILITY VEHICLE EXPRESS CODES - Gidalanga, Marielle Clave; Demeterio, Feorillo Petronillo A; Belacho, Catherine D (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
In Metro Manila, there are two sets of coded language that baffle and amuse their observant bystanders: the Filipino gay language and the idiom used by the UV Express drivers. Through a reconstructive contextualization and reverse engineering of 100 randomly collected Filipino gay words and another 100 randomly collected UV Express codes, this paper compared and contrasted their themes and creations. This paper is significant in offering a comprehensive listing and descriptions of the processes involved in the creation of Filipino gay words. This paper is also significant in being the first academic journal article that deals with the UV Express codes of Metro Manila. Furthermore, the methodology of this paper in studying either the Filipino gay language or the Metro Manila UV Express codes can be used in studying the variant Filipino gay languages in other places of the Philippines.